Folding techniques for designers : from sheet to form - Jackson, Paul, 1956- (London : Laurence King, 2011)
Many designers use folding techniques in their work to make three-dimensional forms from two-dimensional sheets of fabric, cardboard, plastic, metal, and many other materials. This unique book explains the key techniques of folding, such as pleated surfaces, curved folding and crumpling. An elegant, practical handbook, it covers over 70 techniques explained by clear step-by-step drawings, crease-pattern drawings, and specially commissioned photography.